Made in France? The (re-)invention of 'Mai 68'. Issue 4 (4th July 2017) - Krawatzek, Félix
Abstract: Whenever young people protest, references to the French 'Mai 68' are quickly made. For nearly 50 years, former activists and journalists have turned events in the Latin Quarter in Paris into the main symbol for the potential of youth to pressure governments. Western European politicians and scholars easily index 'Mai 68' as the positive core of 'European Memory'. French accounts during the historical moment initially emphasized, however, the global experience of student unrest. Such interpretations understood mobilization in Mexico, Poland and Nigeria as sharing one horizon of expectation and turned worldwide anti-authoritarian student unrest into an interpretive frame. With the unfolding of events in France, the French narrative shifted from a globally experienced present to a nationally framed 'évènement' of the past. This shift from lived experience to memory turned the student mobilization into a succession of French historical events coined 'les évènements de mai-juin 68'. The commemoration of French events as a paradigmatic case sidelined mobilization in other European, Asian, African and Latin American countries. Meanwhile, this nationalization gave way to a pacified Franco-centred narrative which could be juxtaposed to the European memory scale whilst neglecting its internal contradictions stemming from the diverse European and global peripheries.